Preferential Involvement of BRCA1/BARD1, Not Tip60/Fe65, in DNA Double-Strand Break Repair in Presenilin-1 P117L Alzheimer Models. (21st February 2022) - Authiat, Marcella M.; Gruz-Gibelli, Emmanuelle; Colas, Julien; Bianchi, Estelle; Garcia-Arauzo, Marta; Marin, Pascale; Herrmann, François R.; Savioz, Armand
Abstract : Recently, we showed that DNA double-strand breaks (DSBs) are increased by the A β 42 -amyloid peptide and decreased by all-trans retinoic acid (RA) in SH-SY5Y cells and C57BL/6J mice. The present work was aimed at investigating DSBs in cells and murine models of Alzheimer's disease carrying the preseniline-1 (PS1) P117L mutation. We observed that DSBs could hardly decrease following RA treatment in the mutated cells compared to the wild-type cells. The activation of the amyloidogenic pathway is proposed in the former case as A β 42 - and RA-dependent DSBs changes were reproduced by an α -secretase and a γ -secretase inhibitions, respectively. Unexpectedly, the PS1 P117L cells showed lower DSB levels than the controls. As the DSB repair proteins Tip60 and Fe65 were less expressed in the mutated cell nuclei, they do not appear to contribute to this difference. On the contrary, full-length BRCA1 and BARD1 proteins were significantly increased in the chromatin compartment of the mutated cells, suggesting that they decrease DSBs in the pathological situation. These Western blot data were corroborated by in situ proximity ligation assays: the numbers of BRCA1-BARD1, not of Fe65-Tip60 heterodimers, were increased only in the mutated cell nuclei. RA also enhanced the expression of BARD1 and of the 90 kDa BRCA1 isoform. The increased BRCA1 expression in the mutated cells can be related to the enhanced difficulty to inhibit this pathway by BRCA1 siRNA in these cells. Overall, our study suggests that at earlier stages of the disease, similarly to PS1 P117L cells, a compensatory mechanism exists that decreases DSB levels via an activation of the BRCA1/BARD1 pathway. This supports the importance of this pathway in neuroprotection against Alzheimer's disease.